Ownership Governance Practices and their Influence on Family Businesses Financial Performance - Ramirez, Jose B. Betancourt; Lagos Cortés, Diógenes; Gómez-Betancourt, Gonzalo (International Journal of Economics and Financial Issues, 2020)
Ownership is usually a system assumed implicit in the dynamics of management of enterprises, but it actually deserves more attention than a periodic control in the yearly general shareholder´s assembly. Empowerment of owners is required given the magnitude of decisions they make in terms of capital and business purpose, and not just delegate it to the Board or the CEO. Despite the relevance of the topic, there is a gap in the literature of corporate governance in family business from the ownership dimension. This longitudinal study uses a quantitative approach with an explanatory scope that pretends to answer the question: Do shareholders corporate governance practices and family control influence financial performance on businesses? 104 public companies were analyzed and 36.5% of them were identified as family businesses, using data from National Registry of Values and Issuers, which also responded the country Code ’survey of Colombia in the period 2008 to 2014. Data was processed with student’s t test and Random Effects analysis that is a panel data technique. Results shown that family and non-family businesses have significant differences in ownership governance practices, but no significant relationship were identified between corporate governance practices of shareholders or family control with financial performance. Keywords: shareholders, ownership, corporate governance, practices, family business, financial performance JEL Classifications: G30, G34, L25 DOI: https://doi.org/10.32479/ijefi.9170